Pengaruh Parenting Pada Orang Tua Terhadap Pola Asuh Anak Usia Dini - Masruroh, Fitriatul; Wahyuningsih, Riris; Halima, Anita Nur (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Involving parents in the implementation of education (parenting education), especially at home is one solution that can improve the quality of education and the quality of parenting in the family, which is carried out from an early age. Parents are the creative center for their children, so we as parents should be creative in raising children. The goal of it all is for children to grow and develop into creative children. Parenting is aligning education at home and in PAUD in the form of non-formal education activities. The purpose of the activities carried out by this school in the form of a parenting program are insights and information from parents related to the growth and development of children. This research is a type of experimental research with the research design Pretest-Posttest One Group Design. The population of this study were the parents of 26 students. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis using the t-test. Based on the results of the descriptive analysis, the average pretest- posttest was 65 before using parenting (pretest) and 80 after using parenting (posttest). at α of 0.05 (sign α) thus it can be concluded that H1 is accepted. So, in other words, there is a difference after parenting to the upbringing of parents in the Gepuro NU Muslimat Kindergarten.